Comparative study of rans turbulence models for impinging jet simulations - Vittori, Felipe; Rojas-Solorzano, L.; Pavageau, M. (Memorias del Congreso ASME USB 2011: IX CONGRESO ANUAL DE INGENIERÍA ASME USB 2011 03, 04 Y 05 de junio, 2011, Caracas - Venezuela, 2011)
Impinging plane jets are flow configurations with applications in many fields. The ability of several turbulence models to simulate this kind of flow was assessed. The numerical results were compared with the data of Cooper et al. (1993) for Re=7.0 104 and a jet nozzle aspect ratio H/D=6, and Re=2.3 104 and H/D=2. The SST, RSM-ε and RSM-BSL turbulence models were chosen because of their capability to predict flows with high streamline curvature and their expected good accuracy on near wall flow. The results show that the SST and RSM- ε perform better than the RSM-BSL in the prediction of the mean velocity profiles in the wall-jet and impact zone. The profiles of turbulent energy were particularly difficult to reproduce. All the turbulence models considered here exhibit a similar behavior with respect to the profiles of turbulent energy. The paper shows again the complexity of turbulent impinging jets and the relevant open challenges in CFD
Keywords: Research Subject Categories::TECHNOLOGY::Engineering mechanics; mechanical engineering